Development of Dextran-Coated Magnetic Nanoparticles Loaded with Protocatechuic Acid for Vascular Inflammation Therapy - Maria Anghelache; Mihaela Turtoi; Anca Roxana Petrovici; Adrian Fifere; Mariana Pinteala; Manuela Calin (MDPI AG, 2021)
Vascular inflammation plays a crucial role in the progression of various pathologies, including atherosclerosis (AS), and thus it has become an attractive therapeutic target. The protocatechuic acid (PCA), one of the main metabolites of complex polyphenols, is endowed with anti-inflammatory activity, but its formulation into nanocarriers may increase its bioavailability. In this study, we developed and characterized dextran shell‒iron oxide core nanoparticles loaded with PCA (MNP-Dex/PCA) and assessed their cytotoxicity and anti-inflammatory potential on cells acting as key players in the onset and progression of AS, namely, endothelial cells (EC) and monocytes/macrophages. The results showed that MNP-Dex/PCA exert an anti-inflammatory activity at non-cytotoxic and therapeutically relevant concentrations of PCA (350 μM) as supported by the reduced levels of inflammatory molecules such as MCP-1, IL-1β, TNF-α, IL-6, and CCR2 in activated EC and M1-type macrophages and functional monocyte adhesion assay. The anti-inflammatory effect of MNP-Dex/PCA was associated with the reduction in the levels of ERK1/2 and p38-α mitogen-activated protein kinases (MAPKs) and NF-kB transcription factor. Our data support the further development of dextran shell-magnetic core nanoparticles as theranostic nanoparticles for guidance, imaging, and therapy of vascular inflammation using PCA or other anti-inflammatory compounds.